Effects of Forestry on Carbon Emissions in China: Evidence From a Dynamic Spatial Durbin Model - Li, Zaijun; Mighri, Zouheir; Sarwar, Suleman; Wei, Chen (Frontiers in Environmental Science, 2021)
Research has proved the significance of forests in controlling carbon emissions, however, our research sheds light on the management of existing forests to combat climate change. To examine the role of forestation and forest investment activities, dynamic spatial techniques are used for 30 provinces of China. The results suggest that forest investment and management not only reduce carbon locally but also in neighboring provinces. Furthermore, the findings of the current study confirmed that forest investment is the most viable practice to control carbon emissions in China instead of just increasing total forest area. Reforms regarding the management of forests would be a good policy for both pollution reduction and employment generation.